Với [tex]x \rightarrow +\infty[/tex]
[tex]\frac{(2x^3-3x)^2-x^4-1}{2x^3-3x-\sqrt{x^4+1}}=\frac{4x^6+9x^2-13x^4-1}{2x^3-3x-\sqrt{x^4+1}}=\frac{4+\frac{9}{x^4}-\frac{13}{x^2}-\frac{1}{x^6}}{\frac{2}{x^3}-\frac{3}{x^5}-\sqrt{\frac{1}{x^8}+\frac{1}{x^12}}}[/tex]
=> [tex]\lim_{x \rightarrow +\infty}\left ( 2x^3-3x+\sqrt{x^4+1} \right )=\lim_{x \rightarrow +\infty}\frac{4+\frac{9}{x^4}-\frac{13}{x^2}-\frac{1}{x^6}}{\frac{2}{x^3}-\frac{3}{x^5}-\sqrt{\frac{1}{x^8}+\frac{1}{x^{12}}}}=+\infty[/tex]
Với [tex]x \rightarrow -\infty[/tex]
[tex]\lim_{x \rightarrow +\infty}\left ( 2x^3-3x+\sqrt{x^4+1} \right )=\lim_{x \rightarrow +\infty}\frac{4+\frac{9}{x^4}-\frac{13}{x^2}-\frac{1}{x^6}}{\frac{2}{x^3}-\frac{3}{x^5}+\sqrt{\frac{1}{x^8}+\frac{1}{x^{12}}}}=+\infty[/tex]